Comprehensive analysis of the PLXNA3 gene on prognosis and immune characteristics in breast cancer - Wen Sun; Yifan Xu; Qi Qi; Weiya Zhang; Hong Pan; Guangshun Sun; Shui Wang; Wenbin Zhou (Scientific Reports)
Abstract PLXNA3 is a transmembrane protein essential for axon guidance and synapse formation, gaining attention in cancer research for its roles in cell migration, invasion, and signal transduction. However, its biological significance in breast cancer remains underexplored. Here, bulk RNA sequencing and survival analysis revealed that elevated PLXNA3 levels were correlated with increased malignancy and poorer survival in breast cancer. Single-cell RNA sequencing demonstrated that PLXNA3 was predominantly enriched in tumor cell clusters within the tumor immune microenvironment, rather than in immune cell clusters. In vitro experiments further demonstrated that knockdown and overexpression of PLXNA3 significantly altered the proliferative, invasive, and migratory capacities of breast cancer cells. Additionally, the overexpression of PLXNA3 was negatively correlated with immune activation status and served as a predictor of poor response to anti-PD1 immunotherapy. Our findings suggested that high expression of PLXNA3 is associated with poor prognosis in breast cancer and plays a crucial role in cancer immunity, making it a promising novel target for intervention in breast cancer.